1995
DOI: 10.2527/1995.7371888x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of roughage and grain processing in high-concentrate diets on the performance of long-fed Holstein steers1

Abstract: The effects of roughage source and timing of inclusion in high-concentrate diets on feedlot performance were evaluated in each of 2 yr with 144 and 120 long-fed Holstein steers, respectively. Roughage, when included in the diet, was delivered in a built-in-roughage (BIR) pellet supplying 15 and 6% roughage (percentage of DM) or hay crop silage (HCS) supplying 7 and 10% roughage (percentage of DM) for the growing and finishing periods, respectively. The six dietary treatments (two pens each) investigated were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
2
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
4
4
2
7
Order By: Relevance
“…Performance results in this study corroborate data of Turgeon et al (2010), who observed that WSC diets without forage reduced DMI and increased feed efficiency by 3.5% compared with diets that included forage. In another study, which evaluating the use of diets based on WSC without forage, Traxler et al (1995) found no effect on the ADG.…”
Section: Resultsmentioning
confidence: 91%
“…Performance results in this study corroborate data of Turgeon et al (2010), who observed that WSC diets without forage reduced DMI and increased feed efficiency by 3.5% compared with diets that included forage. In another study, which evaluating the use of diets based on WSC without forage, Traxler et al (1995) found no effect on the ADG.…”
Section: Resultsmentioning
confidence: 91%
“…In South America, the use of WSC diets is more recent, but it has been increasing in the last years. Previous studies have shown that animals fed WSC diets are more efficient (Traxler et al, 1995;Turgeon et al, 2010). However, most of the studies on WSC diets used taurine cattle, and only a few were carried out using Bos taurus indicus.…”
mentioning
confidence: 99%
“…Num trabalho de validação do CNCPS, que faz parte do nível 2 do NRC (1996), o programa superestimou em 10% o ganho de peso de bovinos em pastagem temperada em função do consumo de energia metabolizável . Para bovinos em confinamento, o NRC (1984) subestimou em 4% o consumo de matéria seca e em 12,4% o ganho de peso (Traxler et al, 1995), e o NRC (1996) subestimou a eficiência alimentar (ganho/consumo) em 13 e 23%, pelos níveis 1 e 2 do mesmo (Lana et al, 1997).…”
Section: Resultsunclassified